Peningkatan Hasil Belajar Peserta Didik dalam Keterampilan Menyimak Melalui Model Pembelajaran Bamboo Dancing Kelas IV SDN 3 Padang Panjang Barat Kota Padang Panjang - Yezeeka, Viona Putri; Alwi, Nur Azmi; Yenti, Yesni; Chandra, Chandra (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is based on the low learning outcomes of students in listening skills. Students tend to look bored and passive while listening to the learning process. The lack of concentration of students when listening to learning is one of the obstacles in achieving optimal learning outcomes. This research aims to improve the learning outcomes of students in listening skills through the Bamboo Dancing model. This research is Class Action Research (PTK) with a qualitative and quantitative approach. Research is carried out in two cycles consisting of planning, implementation, observation, and reflection stages. The subjects of this study were 28 class IV students. The results of the study showed an increase in the aspect of the teaching module of cycle I with an average of 87,46 %, and an increase in cycle II with an average of 91,67 % very good (SB). In terms of teacher activity cycle I with an average of 90,62% very good (SB), and increased in cycle II with an average of 93,75% very good (SB). In the aspect of student activity in cycle I with an average of 85.94 good (B), and increased in cycle II 93.75 very good (SB). As well as the learning results of students in cycle I with an average of 78.05% enough (C), and increased in cycle II 91.78 very good (SB). Based on the data, it can be concluded that by using the Bamboo Dancing learning model, the learning outcomes of students in class IV of SDN 3 Padang Panjang Barat can be improved